PELAKSANAAN LELANG BARANG SITAAN KEJAKSAAN NEGERI SUMBAWA BESAR - ELMA OLIVIA GRACELDA; Rina Khairani Pancaningrum (Private Law, 2023)
The Prosecutor's Office in terms of confiscating evidence for the interests of the State, can act specifically, namely the prosecutor as the executor of this authority is authorized as a public prosecutor and carries out court decisions, and other powers based on law. The purpose of this research is to find out and analyze the civil law relationship between the district attorney, bidders, and the auction winner in a lawsuit over the auction object after the auction. This study uses normative research methods with the function of providing juridical arguments when there is emptiness, ambiguity, and conflicting norms. The formulation of the problem in this study is how is the civil law relationship between the State Attorney, Bidders, auction winners, and the KPKL in carrying out the auction at the Sumbawa Besar District Attorney's Office and what are the civil law responsibilities of the State Attorney, Auction Winners and KPKNL for claims for auction objects after the auction.